Simulation of Dynamic System Model in the Development of Green Environmental Tourism to Increase Economic Growth in Pangandaran - Dedeh Maryani (Jurnal Ilmu Pemerintahan Widya Praja, 2017)
Pangandaran as a new autonomous region has a great potential in tourism, Pantai Pangandaran, Cagar Alam Pananjung, Pantai Batu Hiu, Pantai Batu Karas, Pantai Madasari, Green Canyon, Citumang. Therefore, this vision is: "Pangandaran in 2025 became a worldwide tourism district, a place to stay safe and comfortable based on religious norms".In Pantai Pananjung tourism, there are many things remaining to be managed. They are road infrastructure and other facilities such as garbage management, street vendors and parking arrangement.To realize this vision, it is necessary to create a model that is most appropriate to develop tourism through the development of green tourism. Therefore, the authors conduct research on "Simulation Model Dynamic Systems Development of Sustainable Tourism to boost economic growth in Pangandaran".The purpose of this study is to determine the model of dynamic systems development of Pantai Pangandaran tourism need to be implemented by the local government. The research was conducted by applying dynamic system simulations to determine the conditions and characteristics of the place within the next 10 years oriented to social, economic and environmental. This study is a combination of exploratory and causal research.The result shows that the development of tourism of Pantai Pangandaran is influenced by socio- economic conditions and the environment and the ability of financial resources. They have implications for economic growth. Socio-economic factors such as national and local Budget investment and the 3rd parties to conduct the development of sustainable tourism. It means that the cooperation must be conducted among the Government, the Local Government and the third party to allow eligibility financially to carry out sustainable development. However, sustainable tourism development is inseparable from the preservation of the environment. Therefore, the construction is obliged to implement the environmental analysis that is capable in overcoming garbage as the impact of increasing population and a number of visitors. Therefore, the pollution of air, soil and water can be prevented. Furthermore, an increase in investment, the productivity of agriculture, industry and service sectors increased will increase people's income and foreign exchange area and the GDP as well as the ability of curbing inflation and ultimately to increase regional economic growth.Keyword : Dynamic system, tourism, green environmental, economic growth